Hierarchy of hormone action controlling apical hook development in Arabidopsis - Gallego Bartolomé, Javier (2011)
The apical hook develops in the upper part of the hypocotyl when seeds buried in the soil germinate, and serves to protect cotyledons and the shoot apical meristem from possible damage caused by pushing through the soil. The curvature is formed through differential cell growth that occurs at the two opposite sides of the hypocotyl, and it is established by a gradient of auxin activity and refined by the coordinated action of auxin and ethylene. Here we show that gibberellins (GAs) promote hook development through the transcriptional regulation of several genes of the ethylene and auxin pathways in Arabidopsis. The level of GA activity determines the speed of hook formation and the extent of the curvature during the formation phase independently of ethylene, probably by modulating auxin transport and response through HLS1, PIN3, and PIN7. Moreover, GAs cooperate with ethylene in preventing hook opening, in part through the induction of ethylene production mediated by ACS5/ETO2 and ACS8.